Can the Onset of Type 2 Diabetes Be Delayed by a Group-Based Lifestyle Intervention in Women with Prediabetes following Gestational Diabetes Mellitus (GDM)? Findings from a Randomized Control Mixed Methods Trial - Angela O’Dea; Marie Tierney; Brian E. McGuire; John Newell; Liam G. Glynn; Irene Gibson; Eoin Noctor; Andrii Danyliv; Susan B. Connolly; Fidelma P. Dunne (Journal of Diabetes Research)
Objective. To evaluate a 12-week group-based lifestyle intervention programme for women with prediabetes following gestational diabetes (GDM). Design. A two-group, mixed methods randomized controlled trial in which 50 women with a history of GDM and abnormal glucose tolerance postpartum were randomly assigned to intervention (n=24) or wait control (n=26) and postintervention qualitative interviews with participants. Main Outcome Measures. Modifiable biochemical, anthropometric, behavioural, and psychosocial risk factors associated with the development of type 2 diabetes. The primary outcome variable was the change in fasting plasma glucose (FPG) from study entry to one-year follow-up. Results. At one-year follow-up, the intervention group showed significant improvements over the wait control group on stress, diet self-efficacy, and quality of life. There was no evidence of an effect of the intervention on measures of biochemistry or anthropometry; the effect on one health behaviour, diet adherence, was close to significance. Conclusions. Prevention programmes must tackle the barriers to participation faced by this population; home-based interventions should be investigated. Strategies for promoting long-term health self-management need to be developed and tested.